DEIXIS USED BY AN ENGLISH TEACHER IN CLASSROOM INTERACTION: A PRAGMATIC STUDY IN SENIOR HIGH SCHOOL - Amalia Putri, Afifah; Muljanto, Setia; Hidayat, Muhamad Taufik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Language constitutes the primary medium through which teachers and students construct meaning in educational settings. Among the most fundamental pragmatic properties of classroom language is deixis, expressions whose interpretation depends entirely on the context of utterance. The present study investigates the types of deixis employed by an English teacher during classroom interaction at a senior high school in Garut, West Java, and examines why a specific type prevails. A qualitative descriptive approach was used, with data gathered through passive participant observation and audio-visual recording across two lesson sessions on conjunction and narrative text. All deictic expressions in the teacher’s utterances were classified into five categories based on Levinson’s (1983) framework: person deixis, time deixis, place deixis, discourse deixis, and social deixis. A total of 299 deictic tokens were identified. The data contained all five types of deixis. Person deixis was the most dominant with 164 occurrences (54.8%), followed by time deixis with 51 (17.1%), discourse deixis with 32 (10.7%), place deixis with 26 (8.7%), and social deixis with 24 (8.0%). This is due to the interpersonal nature of instructional discourse, the teacher’s inclusive use of first-person plural forms, and the code-mixing between English and Indonesian which broadened the range of personal reference expressions. The findings suggest that personal reference is the dominant vehicle of pedagogical communication in the English classroom.